2013
DOI: 10.1002/jee.20020
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity of Implementation of Research‐Based Instructional Strategies (RBIS) in Engineering Science Courses

Abstract: Background Increasing attention is being paid to improvement in undergraduate science, technology, engineering, and mathematics (STEM) education through increased adoption of research-based instructional strategies (RBIS), but high-quality measures of faculty instructional practice do not exist to monitor progress.Purpose/Hypothesis The measure of how well an implemented intervention follows the original is called fidelity of implementation. This theory was used to address the research questions: What is the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
127
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 47 publications
3
127
0
Order By: Relevance
“…The two most cited barriers to implementing RBIS's in core electrical engineering courses included 1) concern for requiring too much class time which could potentially undermine their efforts to cover the course content and 2) the cost of preparation time to implement RBIS 1 . As a result, engineering education researchers were urged to provide details of implementation and the underlying educational research principles in addition to evidence of efficacy when attempting to convince STEM faculty to apply RBIS's in their classroom 2 . Potential adopters should seek out the background information to make informed decisions about how to properly implement the RBIS within the course and achieve the desired student outcomes 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two most cited barriers to implementing RBIS's in core electrical engineering courses included 1) concern for requiring too much class time which could potentially undermine their efforts to cover the course content and 2) the cost of preparation time to implement RBIS 1 . As a result, engineering education researchers were urged to provide details of implementation and the underlying educational research principles in addition to evidence of efficacy when attempting to convince STEM faculty to apply RBIS's in their classroom 2 . Potential adopters should seek out the background information to make informed decisions about how to properly implement the RBIS within the course and achieve the desired student outcomes 2 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, engineering education researchers were urged to provide details of implementation and the underlying educational research principles in addition to evidence of efficacy when attempting to convince STEM faculty to apply RBIS's in their classroom 2 . Potential adopters should seek out the background information to make informed decisions about how to properly implement the RBIS within the course and achieve the desired student outcomes 2 . Furthermore, the obstacles impeding wide spread integration into the engineering education seem to occur at later stages of adoption beyond awareness and implementation such as a sustained effort to continue the use of the RBIS or discontinue 1,3 .…”
Section: Introductionmentioning
confidence: 99%
“…While the spread of CCPS has been the most far reaching spread of RBIS, other RBIS are also spreading across the program. Classroom response systems (i.e., clickers) and peer instruction [4] are being used in 16 SIIP-affiliated courses, most of which had not been using clickers before SIIP. The use of an adaptive learning and testing platform is now being used in 10 SIIP-affiliated courses.…”
Section: Spreading Innovation Through Faculty Communities Of Practicementioning
confidence: 99%
“…Studies guided by the Diffusion of Innovations have shown that faculty are generally aware of Research-Based Instructional Strategies (RBIS), but they either fail to incorporate them into their teaching methods or quickly abandon their adoption of RBIS shortly after beginning to use them [2][3][4][5][6] . The first challenge suggests that faculty need to perceive the value that RBIS bring to their own classrooms 6 .…”
Section: Introductionmentioning
confidence: 99%
“…From a practical standpoint, it is important to understand the relationship between instruction, active learning, and engagement so that strategies can be tailored to provide appropriate learning experiences for students. Different forms of instructional strategies (Borrego, et al, 2013) may engage students in different ways, producing different cognitive, affective, and behavioral processes better suited for one type of learning over another.…”
Section: Introductionmentioning
confidence: 99%